2018
DOI: 10.1101/290734
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast calcium transients in neuronal spines driven by extreme statistics

Abstract: Extreme statistics describe the distribution of rare events that can dene the timescales of transduction within cellular microdomains. We combine biophysical modeling and analysis of live-cell calcium imaging to explain the fast calcium transient in spines. We show that in the presence of a spine apparatus (SA), which is an extension of the smooth endoplasmic reticulum (ER), calcium transients during synaptic inputs rely on rare and extreme calcium ion trajectories. Using numerical simulations, we predicted th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Dendritic spines have a unique set of shapes and recently the size and shape distribution of spines has been linked to their physiological function ( Hering and Sheng, 2001 ; Berry and Nedivi, 2017 ). Additionally, only ∼14% of spines have a specialized ER known as the SpApp ( Basnayake et al, 2018 Preprint ; Jedlicka et al, 2008 ), which serves as a calcium store ( Wuytack et al, 2002 ; Jedlicka et al, 2008 ). Indeed, calcium dynamics in dendritic spines are quite complex.…”
Section: Introductionmentioning
confidence: 99%
“…Dendritic spines have a unique set of shapes and recently the size and shape distribution of spines has been linked to their physiological function ( Hering and Sheng, 2001 ; Berry and Nedivi, 2017 ). Additionally, only ∼14% of spines have a specialized ER known as the SpApp ( Basnayake et al, 2018 Preprint ; Jedlicka et al, 2008 ), which serves as a calcium store ( Wuytack et al, 2002 ; Jedlicka et al, 2008 ). Indeed, calcium dynamics in dendritic spines are quite complex.…”
Section: Introductionmentioning
confidence: 99%
“…We also recently revealed that Cx30, one of the two astroglial gap junction channel subunit, which is a determinant of astroglial synapse coverage controlling synaptic efficacy and hippocampal-based memory via an unprecedented non channel function controlling the astroglial coverage of synapses (Pannasch et al, 2014), also controls hippocampal neuronal population bursts and associated convulsive behavior (Pannasch et al, 2019). We report that Cx30 expression is increased in vivo by seizures and that it controls in turn the severity of behavioral seizures.…”
Section: Publicationsmentioning
confidence: 56%
“…Transient molecular activation in many cellular processes, such as gene transcription [1], calcium activity in neuronal protrusion [2] or biochemical pathways associated with a secondary messenger transduction [3] often occur in geometrical restricted micro-compartments, where the initial distribution of the source is well separated from the target site. To guarantee a reliable and fast activation, these processes are carried out by multiple redundant particles [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%